2021
DOI: 10.1007/s10719-021-10021-z
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 S glycoprotein binding to multiple host receptors enables cell entry and infection

Abstract: Graphical abstract The severe acute respiratory syndrome-related coronavirus-2 (SARS-CoV-2) infection displays a wide array of clinical manifestations. Although some risk factors for coronavirus disease 2019 (COVID-19) severity and outcomes have been identified the underlying biologic mechanisms are still not well understood. The surface SARS-CoV-2 proteins are heavily glycosylated enabling host cell interaction and viral entry. Angiotensin-converting enzyme 2 (ACE2) has been identified to be the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 113 publications
0
49
0
Order By: Relevance
“…This protein is exclusively expressed in Langerhans cells (LC)–the first dendritic cells to encounter pathogens entering the body via the mucosa or skin [ 64 ]. Langerin binds COVID-19 glycoprotein glycans; however, it does not mediate transfection of COVID-19 pseudovirions in a T-lymphocyte cell line [ 65 ], rendering its role in COVID-19 infections inconclusive [ 66 ]. Our findings showed evidence consistent with high levels of SFTPD potentially protecting against COVID-19 hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is exclusively expressed in Langerhans cells (LC)–the first dendritic cells to encounter pathogens entering the body via the mucosa or skin [ 64 ]. Langerin binds COVID-19 glycoprotein glycans; however, it does not mediate transfection of COVID-19 pseudovirions in a T-lymphocyte cell line [ 65 ], rendering its role in COVID-19 infections inconclusive [ 66 ]. Our findings showed evidence consistent with high levels of SFTPD potentially protecting against COVID-19 hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Coronaviruses have advanced various mechanisms to identify diverse receptors for their cross- species transmission and expansion. These viruses use a variety of cellular receptors and co- receptors that allow them to infect a wide range of avian and mammalian species ( Trbojević- Akmačić et al, 2021 ; Zhang et al, 2021 ). The spike protein mainly mediates viral entry into host cells ( Huang et al, 2020 ; Trbojević-Akmačić et al, 2021 ; Zhang et al, 2021 ), although several other molecules have been suggested (e.g., C-type lectins, DC-SIGN, L-SIGN) ( Rahimi, 2020 ; Thépaut et al, 2021 ; Jackson et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…These viruses use a variety of cellular receptors and co- receptors that allow them to infect a wide range of avian and mammalian species ( Trbojević- Akmačić et al, 2021 ; Zhang et al, 2021 ). The spike protein mainly mediates viral entry into host cells ( Huang et al, 2020 ; Trbojević-Akmačić et al, 2021 ; Zhang et al, 2021 ), although several other molecules have been suggested (e.g., C-type lectins, DC-SIGN, L-SIGN) ( Rahimi, 2020 ; Thépaut et al, 2021 ; Jackson et al, 2022 ). During maturation, the spike protein is cleaved into receptor binding and membrane fusion subunits (S1 and S2 subunits, respectively) ( Duan et al, 2020 ; Huang et al, 2020 ; Jackson et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“… 4 SARS-CoV-2 entry into host cells is an essential step of viral infectivity and pathogenesis, mediated by the spike glycoprotein S interaction, predominantly with angiotensin-converting enzyme 2 (ACE2). 5 After SARS-CoV-2 binding to a cell surface receptor, receptor transmembrane protease serine 2 (TMPSRR2) cleaves SARS-CoV-2 S glycoprotein between S1 and S2 domains, enabling S1 detachment, conformational changes of S2, and fusion of viral and host cell membrane. 6 Alternatively, SARS-CoV-2 can utilize the endosomal pathway to enter the cells.…”
Section: Introductionmentioning
confidence: 99%